MENINGKATKAN POTENSI BISNIS PETERNAKAN MELALUI PELATIHAN PEMBUATAN GARAM MINERAL BLOK (GMB) PADA PETERNAK SAPI DI GAMPONG JEULIKAT PROVINSI ACEH - Ikhsanunddin; Muslina; Asra; Asmah Savitri; Lia Safrina (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2022)
The cattle farming business in Jeulikat is still done traditionally and the average farmers do not have special understanding and skills in the field of animal husbandry, they only rely on habits that have been passed down from generation to generation both in providing food and in medicine. The purpose of this training is to train cattle breeders in responding to the symptoms of mineral deficiency shown by livestock by making Block Mineral Salts. The activity approach was participatory training to accommodate various responses from the community so that farmers can practice directly according to the instructions given in the training. The results that were shown from the community's response, in addition to farmers being very enthusiastic and participating actively, they were also expect similar activities such as training in making catle feed so that the livestock business can be developed on a large scale.